2023
DOI: 10.1021/acscatal.3c01407
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Supramolecular Photocatalysts for CO2 Reduction with Eight Carbon–Carbon Bonds between a Ru(II) Photosensitizer and a Re(I) Catalyst Unit

Abstract: Supramolecular photocatalysts, wherein redox photosensitizer (PS) and catalyst (CAT) molecules are connected to each other, have been extensively studied because of their high photocatalytic activity in both homogeneous and heterogeneous environments compared with the corresponding mixed systems of separated PS and CAT. A supramolecular photocatalyst RuC2PhC2Re, wherein [Ru­(diimine)3]2+ redox PS and fac-[Re­(diimine)­(CO)3{OC­(O)­OCH2CH2N­(CH2CH2OH)2}] CAT units were spatially separated by a bridging ligand p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The above mechanism is also consistent with the most reported ndings. [44][45][46] In addition to the Ru(II) photoactive units and Re(I) catalytic sites, our MCOF also features two sets of interdigitated covalent organic networks (Fig. 1g).…”
Section: Resultsmentioning
confidence: 99%
“…The above mechanism is also consistent with the most reported ndings. [44][45][46] In addition to the Ru(II) photoactive units and Re(I) catalytic sites, our MCOF also features two sets of interdigitated covalent organic networks (Fig. 1g).…”
Section: Resultsmentioning
confidence: 99%
“…In the photocatalytic system using a supramolecular photocatalyst consisting of the Ru( ii ) photosensitiser and fac -[Re(diimine)(CO) 3 {OC(O)OC 2 H 4 NR 2 }] catalyst units ( RuC2Re ), kinetic studies on the formation processes of the one-electron reduced species (OERS) of the Re unit, which is one of the key intermediates in the initial stage of photocatalytic CO 2 reduction, and its reactivity, were clarified using time-resolved IR (TR-IR) measurements using the pump–probe method and TR-vis measurements using the Randomly Interleaved Pulse Train (RIPT) method (Scheme 1). 46,47 These results clearly indicated that the OERS of RuC2Re is produced by two processes: (1) a fast process lasting several tens of nanoseconds after excitation, which is reductive quenching of the excited state of the Ru unit to yield the OERS of the Ru unit, i.e. , (Ru) − C2Re (Scheme 1, Process (a)), followed by fast intramolecular electron transfer to the Re unit to produce another OERS, i.e.…”
Section: Introductionmentioning
confidence: 96%
“…1–4 Among them, photooxidation of organic substrates and photoreduction of CO 2 have gained a lot of attention in the past decade, as these reactions not only provide a fundamental understanding of photocatalysis but also show promising practical applications. 5–11 For example, oxidative coupling of amines to imines, oxygenation of sulfides to sulfoxides, oxidation of alcohols to carbonyl compounds, and dehydrogenation of N-heterocycles are several basic reactions in organic synthesis, which are also of significant importance in the production of pharmaceuticals and fine chemicals. 12–16 Using light energy to drive these oxidation reactions is believed to be green, sustainable, and economical, especially with earth-abundant catalysts and molecular O 2 as an oxidant in air under mild conditions.…”
Section: Introductionmentioning
confidence: 99%